Polymyalgia rheumatica/giant cell arteritis in a Cambridge general practice. Issue 6492 (10th August 1985) - Kyle, V; Silverman, B; Silman, A; King, H; Oswald, N; Reiss, B; Hazleman, B
Abstract : The aim of this study was to establish the incidence and prevalence of polymyalgia rheumatica/giant cell arteritis in general practice. Patients with this disorder, whether previously diagnosed or not, were ascertained by using a questionnaire administered by interview, and all received full clinical and laboratory assessment. A total of 579 patients aged 65 and over was seen, and 19 (33/1000) had been diagnosed or developed symptoms within the previous eight years. Thus the calculated annual incidence in those aged 65 and over was about 4/1000. The figures from this first large scale study of polymyalgia rheumatica/giant cell arteritis in general practice are much higher than those from studies carried out in hospital. The questionnaire was effective in both identifying known cases of polymyalgia rheumatica/giant cell arteritis and detecting new cases. As this is a treatable disorder, it is important that doctors become aware of how common it is in elderly people.